Chemical constituents from the calyxes of Physalis alkekengi L. var. franchetii (Mast.) Makino. (June 2018) - Lv, Hui; Fu, Chun-Sheng; Hu, Hui-Xin; Wang, Xiao-Ning; Ren, Dong-Mei; Lou, Hong-Xiang; Shen, Tao
Abstract: Phytochemical investigations of the ethanolic extract from the calyxes of Physalis alkekengi L. var. franchetii (Mast.) Makino led to the isolation of n-heptadecanoic acid (1 ), n-pentadecanoic acid (2 ), n-hexadecoic acid (3 ), n-undecanoic acid (4 ), hendecane (5 ), β-sitosterol (6 ), n-octadecanoic acid (7 ), isovanillic acid (8 ), 4-methylgentisic acid (9 ), 2, 3, 4-trihydroxybenzoic acid (10 ), 5, 7-di- O -methylquercetin (11 ), 8-hydroxy-7-methoxycoumarin (12 ), 4, 7-didehydroneophysalin B (13 ), and ( Z )-9, 10, 11-trihydroxy-12-octadecenoic acid (14 ). Their structures were established by extensive analysis of their NMR spectroscopic data and comparison with literature data. In the present research, compounds8 and11 are reported for the first time in the genus Physalis. Compounds10 and12 were firstly isolated from Solanaceae family. Compound9 was isolated from plants for first time. The chemotaxonomic significance of the isolated compounds has been discussed. Highlights: Seven aliphatic derivatives, three benzenoids, one flavonoid, one phenylpropanoid, and two steroids were isolated from Physalis alkekengi var. franchetii . Compounds 8–12 are firstly isolated from genus Physalis. Compounds 10 and 12 are firstly reported from family Solanaceae. Compound 9 is firstly reported in plants.